Model of a Regional Business Cycle Indicatorforthe Province of Warmia and Mazury - Warżała, Rafał (Olsztyn Economic Journal, 2012)
Business cycle analysis at the national level does not have to be consistent with the economic situation of its individual regions. Diversity in the structure and development dynamics of the individual regions isalso reflected in the range of sensitivity to business cycle changes. Anevaluation was conducted of the suitability of multi-dimensional comparative analysis methods to evaluate the business cycle in the economy on a regional basis based on the example of Warmia and Mazury.The economy of Warmia and Mazury and its sensitivity to macroeconomic disturbances was the subject of the analysis. The business cycle studies by region conducted in Poland are based on so-called "business cycle tests" which are characterised by a high level of subjectivism. They are based on the results of questionnaire-based surveys conducted among entrepreneurs and, as a consequence, it seems justified to build a business cycle indicator for the province of Warmia and Mazury based on "hard" economic data. The proposal of the business cycle indicator for the region of Warmia and Mazury is based on the key economic dimensions for the region. The currently applied methods for elimination of irregular fluctuations and location of turning points were used for designing it. The outcome of the above measures offers the possibility to present the value of the current and prognostic business cycle indicator for Warmia and Mazury with monthly frequency.